Ethics, Moral, and Politics in Teachers’ Virtuous Pedagogical Practice - Husu Jukka; Toom Auli (Emerald, 2025)
Teaching is seen as a morally significant endeavour but there is a lack of clarity about the entire domain. While teachers usually do not develop a refined professional knowledge base or vocabulary of the moral work of teaching (Sanger, 2017) during pre- and in-service teacher education, there is a need to explore more in detail what kind of expertise is required and employed in the moral work of teaching, and how the components of that expertise are related to each other. The purpose of our theoretical chapter is not to present the “foreground”, that is the results of “what works” but instead to highlight the “background” of teaching profession. We note that the complexities of teaching can be structured through the relational viewpoints of ethical principles, moral judgments, and virtuous policies. From these three standpoints, that often appear separate and disconnected, we try out a constructive synthesis. Our framework denotes that teaching is a peculiar kind of relationship that brings with it special ethical guidelines, moral judgements, and constant considerations of how to realize human well-being in the real-world dilemmas of teaching.
Approaches to Teaching and Teacher Education: ISATT 40th Anniversary Yearbook